Synergism between narrowband ultraviolet B phototherapy and etanercept for the treatment of plaque‐type psoriasis. (8th July 2013) - Calzavara‐Pinton, P.G.; Sala, R.; Arisi, M.; Rossi, M.T.; Venturini, M.; Ortel, B.
<x xml:space="preserve">Abstract</x> What's already known about this topic? Previous studies have reported that the combination of etanercept (ETN) with narrowband ultraviolet B (NB‐UVB) improves the therapeutic result in patients with psoriasis who were not satisfactorily responsive to ETN alone administered at dosages of 50 mg once or twice weekly. However, it is unclear if this combination is more effective than NB‐UVB phototherapy alone. What does this study add? The combination of etanercept with NB‐UVB has a synergistic effect for clearing plaque‐type psoriasis previously unresponsive to ETN and NB‐UVB phototherapy alone. The clearance rate is very high in a very short time without short‐term adverse effects. See also the Commentary by Hönigsmann